Effects of glycerol and ractopamine hcl (paylean) on growth performance, carcass characteristics, and loin quality of finishing pigs - A W Duttlinger; Michael D Tokach; Steven S Dritz; Terry A Houser; K J Prusa; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 1,054 barrows and gilts (PIC, initially 207.8 lb) were used in a 28-d study to determine the influence of glycerol and ractopamine HCl (Paylean) on growing-finishing pig performance, carcass characteristics, and loin quality. The experiment was conducted in a commercial swine research facility in southwest Minnesota. Pigs were blocked by weight and randomly allotted to 1 of 4 dietary treatments with 10 replications per treatment. Pigs were fed corn-soybean meal-based diets. Dietary treatments were arranged in a 2 × 2 factorial with main effects of glycerol (0 or 5%) and ractopamine HCl (0 or 6.75 g/ton). Overall (d 0 to 28), there were no glycerol × ractopamine HCl interactions (P>0.10) observed for growth performance. Pigs fed dietary glycerol had improved (P<0.04) F/G, but ADG and ADFI (P>0.40) were not affected. Pigs fed diets with added ractopamine HCl had improved (P<0.01) ADG and F/G with a tendency (P>0.08) for lower ADFI than pigs fed diets with no ractopamine HCl. For carcass characteristics, there were glycerol × ractopamine HCl interactions observed (P<0.05) for percent yield and fat free lean index (FFLI). Adding either ractopamine HCl or glycerol to the control diet increased yield and FFLI; however, there were no additive effects when the combination of glycerol and ractopamine HCl was fed. Pigs fed ractopamine HCl had increased (P<0.04) HCW, yield, loin depth, and FFLI. There was a glycerol × ractopamine HCl interaction (P<0.01) observed for loin chop drip loss. Loin chop drip loss was numerically improved when glycerol and ractopamine HCl were added separately to the control diet; however, loin chop drip loss numerically decreased when the combination of glycerol and ractopamine HCl was fed. Glycerol did not affect (P>0.22) loin characteristics. Ractopamine HCl tended to improve (P<0.08) sirloin chop a* (redness) color. Neither ractopamine HCl nor glycerol influenced iodine value of belly fat, jowl fat, or backfat. In conclusion, pigs fed 5% glycerol had improved F/G, whereas pigs fed ractopamine HCl had improved growth and carcass characteristics and a tendency for improved loin a* color.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Finishing pigs; Glycerol; Ractopamine HCl